A Post-Reflation Monetary Framework for Japan - Stone, Mark (IMF Working Papers; Working Paper ;, 2005)
Modifications to Japan's monetary policy framework will be needed as positive inflation resumes because the current monetary regime and operations are tailored to ending deflation. The paper suggests that the monetary regime should move from an "anti-deflation" objective to an inflation objective, complemented by a shift of monetary operations from a quantitative operating target to an interest rate target. There are also questions about the timing of these shifts and the particulars of such arrangements, but decisive answers are elusive.